IMPLIKATUR: FUNGSI TINDAK TUTUR DALAM THE BIG BANG THEORY - Nico Harared (Pujangga: Jurnal Bahasa dan Sastra, 2017)
The research basically aims at describing implicature utterances and implicature strategy of the speech acts and its types of utterance used in the situation comedy series of The Big Bang Theory seen from the Pragmatics point of view. The data is analyzed and described qualitatively by examining the correlation of the implicature strategy of the speech acts and its types of utterance. The data of this research is the implicature utterances of the characters, particularly the ones that appear in each type of utterance (i.e.,declarative, interogative and imperative) and types of speech act (i.e. representative, expressive, directive, and commissive). The source of data is face-to-face conversations among characters who are Physicists and one friend work as waiter. The data is taken from the conversations in the 20 series of three seasons of the situation comedy series of The Big Bang Theory. Findings have shown that implicature utterances among characters by exemplifying declarative, interrogative and imperative. Implicature strategy of the speech acts and its types of utterancethat is subcategorized into several types of utterance of speech act, namely: representative, directive and expressive.